The Prediction of Prostate Cancer Using Different Artificial Neural Network Models with The Help of Prostate Specific Antigen - Kaya, Mehmet Onur; Çolak, Cemil; Özdemir, Enver (İnönü Üniversitesi, 2013)
In this study, with the help of prostate specific antigen PSA values, patients with prostate cancer and without prostate cancer werepredicted by different artificial neural networks ANN models. The study that was carried out retrospectively with 203 men was achievedin Department of Gazi University Faculty of Medicine, Department of Urology, Ankara, Turkey. The formation of prostate cancer wasinvestigated, and some variables were used in the diagnosis of prostate cancer. ANN models were trained with different trainingalgorithms. 9 process elements have been used in input layer. The output layer of value, the presence or absence of prostate cancer, wasaccording to the PSA values. Trying out different ANN models and learning algorithms, the best results were achieved. ANN models wereestimated using feed-forward back propagation network. Of the ANN models in the study, the best ANN model had determinationcoefficient R2 of 0.75 and mean squared error MSE of 0.07, respectively. Different ANN models can give promising results to predictprostate cancer with the help of PSA. Thence, ANN models may be used in the clinical diagnosis

Bu çalışmada, prostat spesifik antijeni PSA değerlerinin yardımıyla prostat kanseri olan ve prostat kanseri olmayan vakaların yapaysinir ağları YSA modelleri yardımıyla tahmin edilmesi amaçlanmıştır. Çalışma, geriye yönelik veri toplama yöntemi ile 203 erkekbireye ait olup, Fırat Üniversitesi Tıp Fakültesi Üroloji Anabilim Dalı Polikliniği’nden sağlanmıştır. Prostat kanserinin oluşumuna ilişkinPSA tipleri ve prostat kanserinin tanısında kullanılan değişkenler incelenmiştir. YSA, değişik öğrenme algoritmaları kullanılarakeğitilmiştir. Girdi katmanında 9 işlem elamanı kullanılmıştır. Çıktı katmanındaki değişken ise PSA değerlerine göre prostat kanser olupolmaması idi. Değişik YSA modelleri ve öğrenme algoritmaları denenerek, en iyi sonuç elde edilmeye çalışılmıştır. YSA modelleri, ileribeslemeli geriye yayılımlı ağ kullanılarak tahminde bulunulmuştur. Çalışmadaki YSA modellerinde, en iyi açıklayıcılık katsayısı R2 veen küçük hata kareleri ortalaması MSE sırasıyla; 0.75 ve 0.07 olarak bulunmuştur. Yapılan çalışmada değişik YSA modellerinin,PSA’nın yardımı ile prostat kanserinin tahmin edilmesinde daha etkili ve ümit verici sonuçlar verebildiği belirlenmiştir. Böylece İleriyeyönelik klinik tanı sürecinde kullanılabilir olduğu görülmüştür
Prostat Spesifik Antijeni Yardımı ile Prostat Kanserinin Değişik Yapay Sinir Ağı Modelleri ile Tahmini